Screening of USDA Onion Germplasm for Fusarium Basal Rot Resistance - Subhankar Mandal; Christopher S. Cramer (Horticulturae, 2021)
Fusarium basal rot (FBR) caused by Fusarium oxysporum f. sp. cepae (FOC) is a major threat to onion (Allium cepa L.) production and marketing worldwide. Finding new sources of FBR-resistance to develop synthetic cultivars is a priority for onion breeders. As there are no FBR-resistant short-day onion cultivars, 85 U.S. National Plant Germplasm System plant introduction onion accessions that originated from 23 different countries were screened for their FBR susceptibility. To compare FBR susceptibility of these accessions at their seedling and mature bulb stages, a susceptible check cultivar, NuMex Crimson, a partially resistant check cultivar, Serrana and its selected population, Serrana-sel, were included in the study. The seedling screening was performed after inoculating silica-sand media with a virulent FOC isolate ‘CSC-515’ at 1.0 × 104 macroconidia g−1 of sand. Each entry was evaluated twice in growth chambers, and percent survival was adjusted to the number of seedlings that germinated in the uninoculated trays. Mature bulbs produced in the field were screened by inoculating transversely cut basal plates with potato dextrose agar plugs containing spores of the same isolate at 3.0 × 104 macroconidia mL−1. FBR severity and incidence were then calculated after 20 days of incubation. Significant variation was found among the accessions for FBR-susceptibility (p < 0.001) at both the seedling and the mature bulb stages. Two sets of 18 accessions were identified either for their higher seedling survival or higher mature bulb FBR-resistance compared to the checks. Among them, PI 256326 (‘Baia Periforme’, the originator cultivar of ‘Serrana’) had a higher seedling survival than both the checks, and a lower mature bulb severity than the susceptible check. Another accession, PI 656956 (‘S015’), exhibited higher seedling survival than the susceptible check and a low FBR severity (4.3 on a 1 to 9 scale) and incidence (41.7%). These two accessions, which were known previously for their high intra-population heterogeneity and root or bulb resistance for FBR, respectively, show promise for incorporating FBR-resistance into short-day onion cultivars. The cultivar rankings could vary in future studies with a range of FOC isolates due to a high cultivar × isolate interaction as observed in past studies.